Markers for visceral hypersensitivity in patients with irritable bowel syndrome. Issue 8 (11th June 2014) - Ludidi, S.; Mujagic, Z.; Jonkers, D.; Keszthelyi, D.; Hesselink, M.; Kruimel, J.; Conchillo, J.; Masclee, A.
Abstract Background Irritable bowel syndrome (IBS) is a heterogenous disorder with visceral hypersensitivity as important hallmark. It is not known whether IBS patients with visceral hypersensitivity have different epidemiological and clinical characteristics compared with IBS patients without visceral hypersensitivity. Aim of our study was to compare in detail a large group of hyper‐ vs normosensitive IBS patients with respect to epidemiological and clinical characteristics. Methods IBS patients (Rome III criteria) have been recruited for a large‐scale cohort study. All patients from this cohort who underwent a rectal barostat procedure were included and allocated based on those with and without visceral hypersensitivity. Patient demographics, and symptoms were collected using questionnaires (GSRS, HADS, SF‐36) and a 14‐day symptom diary for IBS‐related symptoms. A multivariate logistic regression model was used to identify risk markers for having visceral hypersensitivity. Key Results Ninety‐five normosensitive and 93 hypersensitive IBS patients participated in this study. Hypersensitive patients had significantly higher scores for GSRS abdominal pain (p < 0.05), indigestion, reflux and constipation syndrome (all p < 0.01), and IBS symptom intensity, discomfort (both p < 0.05) and mean symptom composite score (p < 0.01). Age, female sex, and the use of SSRI medication were significantly different between the normo‐ and the hypersensitive IBS patients. However, after adjustment for other risk markers, only increasing age was found to be significantly associated with lower odds for having hypersensitivity (OR 0.97 [95% CI: 0.94; 0.99]). Conclusions & Inferences Apart from more severe symptomatology, hypersensitive IBS patients are characterized by significantly younger age compared with normosensitive IBS patients. The study has been registered in the US National Library of Medicine (http://www.clinicaltrials.gov, NCT00702026).